Genome sequencing reveals a phage in Helicobacter pylori - Lehours, Philippe (2019)
Helicobacter pylori chronically infects the gastric mucosa in more than half of the human population; in a subset of this population, its presence is associated with development of severe disease, such as gastric cancer. Genomic analysis of several strains has revealed an extensive H. pylori pan-genome, likely to grow as more genomes are sampled. Here we describe the draft genome sequence (63 contigs; 26× mean coverage) of H. pylori strain B45, isolated from a patient with gastric mucosa-associated lymphoid tissue (MALT) lymphoma. The major finding was a 24.6-kb prophage integrated in the bacterial genome. The prophage shares most of its genes (22/27) with prophage region II of Helicobacter acinonychis strain Sheeba. After UV treatment of liquid cultures, circular DNA carrying the prophage integrase gene could be detected, and intracellular tailed phage-like particles were observed in H. pylori cells by transmission electron microscopy, indicating that phage production can be induced from the prophage. PCR amplification and sequencing of the integrase gene from 341 H. pylori strains from different geographic regions revealed a high prevalence of the prophage (21.4%). Phylogenetic reconstruction showed four distinct clusters in the integrase gene, three of which tended to be specific for geographic regions. Our study implies that phages may play important roles in the ecology and evolution of H. pylori.